Ozone therapy restores immune dysfunction in refractory idiopathic granulomatous mastitis as a novel potential therapeutic approach. (15th November 2022) - Cabioglu, Neslihan; Cetin Aktas, Esin; Emiroglu, Selman; Tukenmez, Mustafa; Ozkurt, Enver; Muslumanoglu, Mahmut; Igci, Abdullah; Ozmen, Vahit; Deniz, Gunnur; Dinccag, Ahmet S.; Guven, Yusuf I.
Abstract: Immunological dysfunction has been suggested to play a major role in the pathogenesis of idiopathic granulomatous mastitis (IGM). We recently showed that ozone therapy was effective in patients with steroid‐resistant IGM. This study assessed alterations in intracellular cytokine expression patterns in different T‐lymphocyte subsets after ozone therapy in refractory IGM. Peripheral blood T lymphocyte subsets (CD8 +, CD4 +, CD4 + CD25 + CD127 − ) were analyzed via flow‐cytometry for intracellular cytokine expressions IFN‐γ, TNF‐α, IL‐10, and TGF‐β before and after completion of 4‐month systemic ozone therapy. Ozone therapy significantly increased the CD4 + IFN‐γ + ( p  = 0.032), CD4 + TNF‐α + ( p  = 0.028), and the CD8 + TNF‐α + ( p  = 0.012) T cells. In contrast, significant decreases in CD4 + IL‐10 + ( p  = 0.047) and CD8 + IL‐10 + T cells ( p  = 0.022) and CD4 + CD25 + CD127 −//low Treg cells secreting TGF‐β ( p  = 0.005) were found after ozone therapy. When patients were analyzed according to the response to ozone therapy, patients with a complete remission were more likely to have increased CD3 − CD16 + CD56 + natural killer cells ( p  = 0.0027) and decreased CD19 + B lymphocytes ( p  = 0.046) following ozone therapy. Our results suggest that ozone therapy stimulated a T‐helper‐1 response associated with IFN‐γ production and downregulation of TGF‐β expression in CD4 + CD25 + CD127 − Treg cells. These alterations in the immune system following ozone therapy can improve wound healing and restore immune dysfunction in patients with refractory IGM.